The New Nitinol Conformable Self-Expandable Metal Stents for Malignant Colonic Obstruction: A Pilot Experience as Bridge to Surgery Treatment - Roberto Di Mitri; Filippo Mocciaro (The Scientific World Journal)
Introduction. Self-expandable metal stents (SEMS) are a nonsurgical option for treatment of malignant colorectal obstruction also as a bridge to surgery approach. The new nitinol conformable stent has improved clinical outcomes in these kinds of patients. We report a pilot experience with nitinol conformable SEMS placement as bridge to surgery treatment in patients with colorectal obstruction. Materials and Methods. Between April and August 2012, we collected data on colonic nitinol conformable SEMS placement in a cohort of consecutive symptomatic patients, with malignant colorectal obstruction, who were treated as a bridge to surgery. Technical success, clinical success, and adverse events were recorded. Results. Ten patients (7 male (70%)), with a mean age of 69.2 ± 10.1, were evaluated. The mean length of the stenosis was 3.6 ± 0.6 cm. Five patients (50%) were treated on an emergency basis. The median time from stent placement to surgery was 16 days (interquartile range 7–21). Technical and clinical success was achieved in all patients with a significant early improvement of symptoms. No adverse events due to the SEMS placement were observed. Conclusion. This pilot study confirmed the important role of nitinol conformable SEMS as a bridge to surgery option in the treatment of symptomatic malignant colorectal obstruction.